Sinergi Sunatan Massal Berkah, Kuliah Kerja Nyata, dan Peletakan Batu Pertama Gedung Baru dalam Pengajian Akbar Muhammadiyah di Pondok Pesantren Darussalam Ogan Ilir: Masses Circumcision, Real Work Lectures, and New Building Ground Breaking at Ogan Ilir Darussalam Muhammadiyah Boarding School - Ghiffari, Ahmad; Gusmiatun, Gusmiatun; Herudiansyah, Gumar; Yanti, Darma; Asysyauki, Akhmad Hamdi; Saputri, Wulandari; Chairani, Liza; Mayasari, Ni Made Elva; Tanzila, Raden Ayu; Prameswarie, Thia; Oktariza, Rury Tiara; Risdiansyah, Risdiansyah; Ardina, Puri Pratami (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
A fire broke out at the Darussalam Muhammadiyah Ogan Ilir Islamic Boarding School, destroying six surrounding schools. The mass circumcision event was coordinated with the Grand Religious Colloquium and the opening of an educational institution for impoverished students. Thirty-seven children who participated in community service took part in the blessing of mass circumcision. A significant number of officials and community guests of honor attended the event, which included the Deputy Regent of Ogan Ilir, a representative from the Yogyakarta Muhammadiyah Central Leadership, the Chairman of the South Sumatra Muhammadiyah Regional Leadership, the Chancellor of the Muhammadiyah University of Palembang, the PDM Chairman of Ogan Ilir, and representatives from TNI, Polri, the Payaraman sub-district head, and village heads. The session concluded with the attendees' tremendous enthusiasm for the event, for which they had earlier registered. Parallel circumcision initiatives could be undertaken alongside other activities. The Deputy Regent and Muhammadiyah Regional Leader of Ogan Ilir hopes that mass circumcision s will continue and be extended to other districts during the future KKN session. It is crucial to gather details concerning circumcision participants, assess the sufficiency of the number of operators, and establish the best time for the activity.